2023
DOI: 10.1007/s10943-023-01811-w
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Transpersonal Gratitude Scale (TGS) and the Relationship between Transpersonal Gratitude, Spiritual Well-Being and Distress in India

Abstract: This study explores the psychometric properties of the transpersonal gratitude scale (TGS) in the Indian context. It also examines the relationship between transpersonal gratitude, spiritual well-being, and distress. The psychometric properties (reliability and validity) of the TGS were evaluated with the help of two studies. In the first study, exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) reported a four-factor solution. These four factors- expression of gratitude, value of gratitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Gratitude, as a psychological state, leads to a sense of appreciation of life ( Emmons and Shelton, 2002 ). It may be expressed in relation to other people, which is considered an interpersonal approach ( Garg, 2023 ), but may also be transpersonal, when related to non-human entities, such as nature, the transcendent ( Garg, 2023 ), or God ( Emmons and Shelton, 2002 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Gratitude, as a psychological state, leads to a sense of appreciation of life ( Emmons and Shelton, 2002 ). It may be expressed in relation to other people, which is considered an interpersonal approach ( Garg, 2023 ), but may also be transpersonal, when related to non-human entities, such as nature, the transcendent ( Garg, 2023 ), or God ( Emmons and Shelton, 2002 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Acts inspired by gratitude increase social bonds and friendships, and are associated with better levels of life satisfaction ( Lambert et al, 2009 ). Furthermore, transpersonal gratitude increases overall spiritual wellbeing ( Garg, 2023 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In a sample of 411 employees, Mahipalan and Garg ( 82 ) reported that gratitude moderated the relationship between workplace bullying and psychological capital of employees. A study involving 112 female employees in India found that gratitude was linked to family enrichment ( 83 ), and to spiritual well-being and distress ( 84 ). In a sample of healthcare employees in India, Garg et al ( 85 ) concluded that gratitude moderated the relationship between workplace toxicity and turnover intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Expanding on the theme of gratitude, Garg (2022) analyzed the interplay between appreciation and the enrichment of work-life balance among female employees, highlighting the intervening influence of psychological capital. Another study by Garg (2023) concentrated on validating the Transpersonal Gratitude Scale (TGS) and exploring the link between transpersonal appreciation, spiritual wellness, and distress. Also, the investigation led by probed the association between gratitude and vigor among students, investigating the mediating role of resilience.…”
Section: Gratitudementioning
confidence: 99%